Microcontroller based low power led driver with a soft switched sepic converter - Dr.Kavitha P, Kalaiarasan. A, Kishore Kumar B, Ganeshmoorthy G (Mathematical Statistician and Engineering Applications, 2022)
Background: This paper intend an economical design of a low power light emitting diode (LED) driver with a soft switched SEPIC converter and a parallel connected high frequency series L-C resonant inverter. The conferred structure extort a rectifier powered SEPIC derived power factor controller (PFC) which minimize the harmonic distortion of the line current by rising the input power factor. On the load side, a high frequency transformer is embraced for isolation and rectifier to offer proper voltage and current to the load. The design contains a feedback loop to control the switching operation of the SEPIC converter by varying its duty cycle. The soft switching application produces to reduce the noise due to electromagnetic interference (EMI). This inverter is controlled using two sinusoidal pulse width modulation (PWM) signals of 20 kHz. This paper adopts the low cost 8 bit microcontroller to provide the driver advantage of effortlessly coupled system in home automation and remote controlled lamps. The model was simulated using a simulation tool. The total harmonic distortion (THD) of the supply line current is around 10% at 0.98 power factor at the sending end.